Study of Prescribing Pattern and Impact of Pharmaceutical Care in Bronchial Asthmatic Paediatric Patients in a Tertiary Care Teaching Hospital - Kumar, Vengala Bhavan; Thankachan, Tina Mariam; Amanapu, Anuradha; Chandra, Devineni Surya; Krishnan, Sundararajan Parimala (Indian Journal of Pharmacy Practice)
Background: Asthma is a chronic inflammatory disease of increasing prevalence that is a result of genetic predisposition and environmental interaction and one of the most common chronic diseases of childhood. Aim and Objective: The aim is to study the prescribing pattern and impact of pharmaceutical care in bronchial asthmatic paediatric patients. The present study was conducted in RMMCH, Chidambaram. Over a six month period patients who were diagnosed with Bronchial asthma was enrolled and the information was gathered using validated data collection form. The overall asthma cohort included in the study based on inclusion criteria. Subjects under 12 years of age, and who are newly diagnosed and admitted in paediatric wards for Bronchial asthma. Results: A total of 61 patients were included out of which 43 (70.4%) are boys and 18 (29.6%) are girls. β-agonists (Salbutamol, Ipratropium bromide) accounts for highest number of 51 out of 61 prescriptions. Among antibiotics crystalline penicillin was present in highest number of prescriptions (86.8%). Drugs used in RMMCH were compared to various EDL (Essential drug list) which complied with national EDL. The pharmaceutical care outcomes was measured and a significant difference was observed between the lung functions tests (FVC; P=<0.001) and (FEV; P=<0.008). Which indicates the improvement of pharmaceutical care from control (30 without intervention) to test (31 with intervention) group. There is a statistically significant difference between the test and control group at (P=<0.001). Conclusion: Patient education produced a substantial improvement in patient counselling, understanding of their illness and role of medication and its treatment. Pharmaceutical care services provided by the pharmacist improved quality of life, medication adherence in test subjects. Interventions aimed at improving therapeutic outcomes in bronchial asthma.
Keywords: β-agonists; Bronchial asthma; Medication adherence; Pharmaceutical care; Prescribing Pattern; Quality of life